Does emotion recognition change across phases of the ovulatory cycle?. (February 2023) - Rafiee, Yasaman; Stern, Julia; Ostner, Julia; Penke, Lars; Schacht, Anne
Abstract: Recognizing emotions is an essential ability for successful interpersonal interaction. Prior research indicates some links between the endocrine system and emotion recognition ability, but only a few studies focused on within-subject differences across distinct ovulatory cycle phases and this ability. These studies have demonstrated mixed results that might be potentially due to heterogeneity in experimental tasks, methodologies, and lacking ecological validity. In the current study, we investigated associations between within-subject differences in ovarian hormones levels and emotion recognition from auditory, visual, and audiovisual modalities in N = 131 naturally cycling participants across the late follicular and mid-luteal phase of the ovulatory cycle. We applied a within-subject design with sessions in the late follicular and mid-luteal cycle phase, and also assessed salivary progesterone and estradiol in these sessions. Our findings did not reveal any significant difference in emotion recognition ability across two cycle phases. Thus, they emphasize the necessity of employing large-scale replication studies with well-established study designs along with proper statistical analyses. Moreover, our findings indicate that the potential link between ovulatory cycle phases (late follicular and mid-luteal) and emotion recognition ability might have been overestimated in previous studies, and may contribute to theoretical and practical implications of socio-cognitive neuroendocrinology. Highlights: Longitudinal study examining emotion recognition in N = 131 women in the late follicular and mid-luteal phase. No association of ovarian hormone differences in the late follicular versus mid-luteal phase and recognizing facial expressions. No association of within-subject differences in progesterone levels and recognizing threat-related emotions. No association of within-subject differences in ovarian hormones and the modality of expressed emotions.